Los mecanismos innovadores de financiación para el desarrollo y la Cumbre del Milenio +5 - Fernández-Coronado, Ignacio Suárez (Revista Española de Desarrollo y Cooperación, 2023)
Taking into consideration the results of the recent United Nations Summit, the objective of the article is to analyze what conditions are necessary to define an appropriate model for development funding. Finally, the author focuses on the suitability of innovative funding mechanisms to achieve this end.